(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In conditions of market destabilization, there is a growing need to define effective concepts and tools for adapting organizational models of foreign economic activity management in the context of increasing digitalization and increasing instability of the world economy. Changing regulatory conditions, rapid technological breakthroughs and increased competition require enterprises to be flexible and innovative. This is of particular importance for Ukrainian enterprises that are integrating into global markets. All this determines the relevance of defining effective approaches to increasing their competitiveness, efficiency and sustainability. The purpose of the article. The purpose of the study is identification of effective concepts and tools for adapting organizational models of foreign economic activity management to changes in the external environment, which ensure flexibility, competitiveness and sustainable development of the enterprise Methods. The research methodology is based on a comprehensive approach, including the analysis of scientific sources, economic data and modern approaches to the adaptation of foreign economic activity management. Comparative analysis methods were used to assess the effectiveness of organizational models, a systems approach to identify key adaptation tools, as well as modeling methods to develop recommendations. Particular attention is paid to the analysis of innovative technologies, such as artificial intelligence, blockchain and big data, to improve management efficiency. Results. The article examines modern concepts and tools for adapting organizational management models to the challenges of foreign economic activity. The impact of globalization, digitalization, and geopolitical instability on the efficiency of enterprises operating in international markets is examined. Key approaches to adapting foreign economic activity management models are analyzed, including decentralization, customer orientation, and integration of innovative technologies. Practical tools for increasing organizational flexibility and improving the decision-making process are identified. The problems faced by Ukrainian enterprises in the process of integration into global value chains are investigated. The need to develop adaptive organizational models that meet the principles of sustainable development is proven. The need to support the competitiveness and efficiency of Ukrainian enterprises in a dynamic global economic environment is identified. Conclusions. The importance of adapting organizational models of foreign economic activity management to ensure the competitiveness of enterprises in a globalized environment has been proven. It has been determined that the introduction of innovative technologies and flexible management structures will contribute to increasing the efficiency and integration of Ukrainian enterprises into world markets.